2015
DOI: 10.1179/1362171815y.0000000048
|View full text |Cite
|
Sign up to set email alerts
|

Auxiliary energy assisted friction stir welding – status review

Abstract: The present article introduces the auxiliary energy assisted friction stir welding (FSW) processes purported to overcome the shortcomings of the conventional FSW process. The auxiliary energies used for this purpose are thermal energy from electric resistance heat, induction heat, laser, plasma, arc, etc. and mechanical energy in the form of ultrasonic vibration. The state-of-the-art, experimentation and progresses in these FSW variants are surveyed and compiled. The auxiliary energy assisted FSW processes exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 88 publications
(328 reference statements)
0
40
0
Order By: Relevance
“…In order to solve these problems, it is required to develop a FSW process in which the resisting force on the tool is sufficient small during the welding and sound joints can be obtained in the FSW of high melting points or high strength materials. Several preheating methods has been adopted for the purpose of long tool life or preventing defect formation in stir zone, and it is known that reducing of resisting force on the tool and increasing of welding speed is possible by preheating with laser, [8][9][10][11][12] high frequency induction heating, 11,12) ultrasonic vibration, 12,13) arc, 12) heating of stage, 14,15) and so on. However, it is not clarified in detail effect of the preheating on formation of stir zone, material flow behavior and resisting force on the tool.…”
Section: Friction Stir Welding Of Medium Carbon Steel With Laser-prehmentioning
confidence: 99%
“…In order to solve these problems, it is required to develop a FSW process in which the resisting force on the tool is sufficient small during the welding and sound joints can be obtained in the FSW of high melting points or high strength materials. Several preheating methods has been adopted for the purpose of long tool life or preventing defect formation in stir zone, and it is known that reducing of resisting force on the tool and increasing of welding speed is possible by preheating with laser, [8][9][10][11][12] high frequency induction heating, 11,12) ultrasonic vibration, 12,13) arc, 12) heating of stage, 14,15) and so on. However, it is not clarified in detail effect of the preheating on formation of stir zone, material flow behavior and resisting force on the tool.…”
Section: Friction Stir Welding Of Medium Carbon Steel With Laser-prehmentioning
confidence: 99%
“…Recently, this manufacturing process has also improved technologically with the addition of ultrasound waves. This coupled system is promised to reduce processing forces, increase process speed and reduce manufacturing costs [17][18][19] . Apart their different technological purpose, FSP and FSW are correlated processes, as input parameters and phenomena observed during the execution of both manufacturing procedures can be linked to produce similar metallurgical results 11,12,14,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers studies found out the weld quality can be improved by enhancing the plastic flow near the tool by applying additional preheating or presoftening mechanisms on the workpiece. Auxiliary energy was used to assist FSW process to heat/soft the workpiece [17]. The assisting energy used was classified in to two categories, thermal and mechanical energies.…”
Section: Introductionmentioning
confidence: 99%